2014
DOI: 10.1186/1471-2229-14-78
|View full text |Cite
|
Sign up to set email alerts
|

Circadian oscillatory transcriptional programs in grapevine ripening fruits

Abstract: BackgroundTemperature and solar radiation influence Vitis vinifera L. berry ripening. Both environmental conditions fluctuate cyclically on a daily period basis and the strength of this fluctuation affects grape ripening too. Additionally, a molecular circadian clock regulates daily cyclic expression in a large proportion of the plant transcriptome modulating multiple developmental processes in diverse plant organs and developmental phases. Circadian cycling of fruit transcriptomes has not been characterized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 77 publications
1
34
1
Order By: Relevance
“…Contrary to the circadian changes found in the grape transcriptome (Carbonell‐Bejerano et al, ), a lower number of phenylpropanoid metabolites were found to significantly change diurnally compared with primary metabolites (Figure S2). Compounds showing significant diurnal changes clearly differed between contrasting orientations of the same cluster (E vs. EW).…”
Section: Resultscontrasting
confidence: 65%
“…Contrary to the circadian changes found in the grape transcriptome (Carbonell‐Bejerano et al, ), a lower number of phenylpropanoid metabolites were found to significantly change diurnally compared with primary metabolites (Figure S2). Compounds showing significant diurnal changes clearly differed between contrasting orientations of the same cluster (E vs. EW).…”
Section: Resultscontrasting
confidence: 65%
“…For example, it has been described that in broccoli and cabbage the antioxidant activity and the content of phenolics decrease toward the end of the day (Soengas, Cartea, Velasco, & Francisco, ). Moreover, in grapes of Tempranillo, a cultivar with black‐skinned berries, the expression of genes related to phenylpropanoid biosynthesis showed a circadian variation (Carbonell‐Bejerano et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, VviLHY and VviTOC1 did not oscillate, whereas VviRVE1 and VviELF3 of the core clock genes did display a circadian rhythm in grape [84]. The authors attribute the differences in clock gene expression to grape maintaining a simplified clock in ripening fruit.…”
Section: Discussionmentioning
confidence: 99%